2023
DOI: 10.1098/rspb.2023.1305
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the connection between autophagy and heat-stress tolerance in Drosophila melanogaster

Quentin Willot,
Andre du Toit,
Sholto de Wet
et al.

Abstract: Mechanisms aimed at recovering from heat-induced damages are closely associated with the ability of ectotherms to survive exposure to stressful temperatures. Autophagy, a ubiquitous stress-responsive catabolic process, has recently gained renewed attention as one of these mechanisms. By increasing the turnover of cellular structures as well as the clearance of long-lived protein and protein aggregates, the induction of autophagy has been linked to increased tolerance to a range of abiotic stressors in diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…As TOR is a master regulator of growth, which detects cellular levels of amino acids and is inactivated by low levels of amino acids [83], we assumed that both isoleucine deprivation and rapamycin achieved nicotine resistance through TOR suppression. However, other studies have shown that rapamycin treatment improves the heat tolerance of wild-type flies [84] and can improve the maximum thermal temperature (CTmax) withstood by Drosophila Genetic Reference Panel (DGRP) flies [85]. We therefore anticipated that short-term isoleucine deprivation would also increase heat tolerance in our flies, but it did not.…”
Section: 95**mentioning
confidence: 92%
“…As TOR is a master regulator of growth, which detects cellular levels of amino acids and is inactivated by low levels of amino acids [83], we assumed that both isoleucine deprivation and rapamycin achieved nicotine resistance through TOR suppression. However, other studies have shown that rapamycin treatment improves the heat tolerance of wild-type flies [84] and can improve the maximum thermal temperature (CTmax) withstood by Drosophila Genetic Reference Panel (DGRP) flies [85]. We therefore anticipated that short-term isoleucine deprivation would also increase heat tolerance in our flies, but it did not.…”
Section: 95**mentioning
confidence: 92%